Intrusion and extrusion of liquids in highly confining media: bridging fundamental research to applications. Issue 1 (31st December 2022) - Le Donne, Andrea; Tinti, Antonio; Amayuelas, Eder; Kashyap, Hemant K.; Camisasca, Gaia; Remsing, Richard C.; Roth, Roland; Grosu, Yaroslav; Meloni, Simone
ABSTRACT: Wetting and drying of pores or cavities, made by walls that attract or repel the liquid, is a ubiquitous process in nature and has many technological applications including, for example, liquid separation, chromatography, energy damping, conversion, and storage. Understanding under which conditions intrusion/extrusion takes place and how to control/tune them by chemical or physical means are currently among the main questions in the field. Historically, the theory to model intrusion/extrusion was based on the mechanics of fluids. However, the discovery of the existence of metastable states, where systems are kinetically trapped in the intruded or extruded configuration, fostered the research based on modern statistical mechanics concepts and more accurate models of the liquid, vapor, and gas phases beyond the simplest sharp interface representation. In parallel, inspired by the growing number of technological applications of intrusion/extrusion, experimental research blossomed considering systems with complex chemistry and pore topology, possessing flexible frameworks, and presenting unusual properties, such as negative volumetric compressibility. In this article, we review recent theoretical and experimental progresses, presenting it in the context of unifying framework. We illustrate also emerging technological applications of intrusion/extrusion and discuss challenges ahead. Graphical Abstract: uf0001